High salinity wastewater treatment - Linarić, M (Water science and technology : a journal of the International Association on Water Pollution Research, 2013)
The shock effect, survival and ability of activated sludge to acclimatize to wastewater containing different concentrations of NaCl and Na2SO4 were investigated under laboratory conditions. To accomplish this, the potential penetration of a sewage system by seawater as a consequence of storm surge flooding was simulated. The experiments were conducted using activated sludge taken from the aeration tank of a communal wastewater treatment plant and adding different concentrations up to 40 g/L of NaCl and 4.33 g/L of Na2SO4. The effects of salinity on the activated sludge were monitored for 5 weeks based on the values of pH, dissolved oxygen, total suspended solids, volatile suspended solids, sludge volume, sludge volume index, electrokinetic potential, respirometric measurements and enzymatic activity. The addition of salt sharply reduced or completely inhibited the microbial activity in activated sludge. When salt concentrations were below 10 g/L NaCl, microorganisms were able to acclimatize in several weeks and achieve the same initial activity as in raw sludge samples. When the salt concentration was above 30 g/L NaCl, the acclimatization process was very slow or impossible